The Influence of Perceived Security, Usefulness, and Ease of Use on the Adoption of E-Filing by Individual Taxpayers at PT Infineon Technologies Batam - Lanniari HS, Rizki; Rahmadhani, Asha Isma (Journal of Applied Accounting and Taxation, 2025)
This research intends to empirically analyze the influence of perceived security, usefulness, and ease of use on the adoption of e-filing by individual taxpayers at PT Infineon Technologies Batam. This study utilizes a quantitative approach by collecting data through online questionnaires distributed via Slido. The research sample consisted of 95 respondents selected by purposive sampling. The result showed that perceived security, usefulness, and ease of use positively influence the adoption of e-filing. These findings provide valuable input to the Tax Directorate General (TDG) to improve e-filing services. By increasing the perceived security, usefulness, and ease of use on e-filing adoption, the TDG can help taxpayers use the service more actively.